2017
DOI: 10.1177/0263617417735480
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hydrophilicity on adsorption of caffeine onto montmorillonite

Abstract: Some types of montmorillonite containing different interlayer ions were prepared and the changes in the interlayer spacings, the hydrophilicity, and the characteristics of adsorption of caffeine in solution were observed. Ion exchange treatments were performed using Li, Na, K, Rb, Cs, Mg, Ca, Sr, or Ba. As a result, Li-and Na-type montmorillonite showed larger interlayer distance (1.31-1.53 nm), than K, Rb, and Cs-type montmorillonite (1.23-1.26 nm). In the measurement of hydrophilicity using a pulse NMR-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…It is present in beverages such as coffee, teas, chocolates, and soft drinks. The metabolism of this substance is rapid where only a small amount (1-10%) is excreted (Thorn et al 2012;Portinho et al 2017;Beltrame et al 2018;Ptaszkowska-Koniarz et al 2018;Yamamoto et al 2018;González et al 2019). Many pharmaceutical compounds, such as caffeine, are considered water contaminants and classified as emerging pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…It is present in beverages such as coffee, teas, chocolates, and soft drinks. The metabolism of this substance is rapid where only a small amount (1-10%) is excreted (Thorn et al 2012;Portinho et al 2017;Beltrame et al 2018;Ptaszkowska-Koniarz et al 2018;Yamamoto et al 2018;González et al 2019). Many pharmaceutical compounds, such as caffeine, are considered water contaminants and classified as emerging pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…It is also possible to change the naturally hydrophilic character of smectite clay minerals into organophilic, making them act as adsorbents for organic compounds. e intercalation of surfactant cations (quaternary ammonium salts) into layers of clay minerals not only changes the surface properties but also increases the interlamellar distance (basal spacing) of the layers, thus easing the adsorption of organic molecules [42,59,[127][128][129][130][131]. Bentonite (a montmorillonite) and saponite are the most frequently used clays as caffeine adsorbents.…”
Section: Inorganic Adsorbentsmentioning
confidence: 99%
“…Regarding aluminosilicates (Table 9), smectite minerals-such as montmorillonite and saponite and their modifications, organoclays, or thermally treated smectites-show a good caffeine adsorption capacity (99.0-143.7 mg/g), with the advantage of being abundant and low-cost materials [22,43,130,131]. Although aluminosilicates have a low SSA in comparison with activated carbons, sepiolite and bentonite have a good adsorption capacity for caffeine.…”
Section: Inorganic Adsorbentsmentioning
confidence: 99%
“…The water molecules are located in the zeolitic cavities of the interlayer region 21 . In the past, several authors have reported that caffeine can be successfully intercalated in lamellar solids reaching interesting goals [22][23][24][25][26][27]28 . Herein we report the first intercalation of CAF on ZrP, obtaining an intercalation product that has been successfully used to prepare a stable emulsion.…”
Section: Figure 1: Chemical Structure Of Caffeinementioning
confidence: 99%